Packaging technology and digital marketing of fish dempo to increase sales productivity - Andi Sitti Halimah; Andi Abdul Muis; Yushra Yushra (University of Merdeka Malang, 2024)
The BUMDes fish processing business unit group experienced obstacles regarding the function of packaging and how to market digitally in the sale of Dempo fish products. The purpose of this PKM is to create the right packaging to maintain product quality; and expand product marketing areas to increase sales productivity through digital marketing. The method is carried out through training and mentoring in the form of packaging practices with the use of vacuum sealers, the creation of e-commerce sales accounts integrated into social media, and the evaluation stage of activities. The results of this community service activity show an increase in the skills of the partner group in utilizing packaging tools for Dempo fish produced (78%) so that product packaging is more attractive and supports shelf life to maintain product quality. With the packaging technology used, the knowledge of partner group members in understanding the function of packaging that affects marketing has also increased (80%). This has an impact on the increase in sales turnover received through social media owned by members of the partner group. If previously it was known that the sales turnover of this product was IDR 16 million per year or equivalent to IDR 1.3 million per month, then after the PKM activity there was an increase in sales turnover of IDR 2.1 million at the same price within 3 weeks.